Efforts by Law Enforcement Officers to Prevent Illegal Racing that Disturb Order in The Jurisdiction of The Pekalongan City Police - Ridho Tri Wicaksono; Indah Maulani (Universitas Muhammadiyah Surakarta, 2026)
This study discusses the phenomenon of illegal racing in the road area towards the interchange Pekalongan Toll Road, Pekalongan City. This activity violates traffic laws and endangers the safety of road users. This study aims to analyze law enforcement against illegal racing perpetrators and assess the effectiveness of prevention efforts by law enforcement officers. This study uses an empirical juridical approach with a qualitative descriptive method to analyze law enforcement against illegal street racing in Pekalongan City. Data were gathered through interviews at the Pekalongan City District Police, direct observation at the research location, and literature studies, then analyzed qualitatively. The results of the study indicate that police efforts through patrols, enforcement, and socialization still face obstacles, such as limited personnel, low legal awareness, environmental influences, and minimal family supervision, so that synergy between various parties is needed.